Effect of indomethacin on swelling, lymphocyte influx, and cartilage proteoglycan depletion in experimental arthritis. Issue 8 (August 1989) - Pettipher, E R; Henderson, B; Edwards, J C; Higgs, G A
Abstract : The effects of indomethacin on antigen induced arthritis in rabbits have been investigated. Arthritis was induced in the knee joints of sensitised rabbits by intra-articular injection of antigen. Swelling of the joints was measured for 14 days after antigen challenge, and groups of animals were killed on days 1, 7, or 14 for collection of synovial fluids and tissues. Indomethacin (1 mg/kg, three times daily) reduced joint swelling and the prostaglandin E2 concentrations in synovial fluid. In addition, indomethacin increased the loss of proteoglycan from articular cartilage and the numbers of lymphocytes in the inflamed synovial lining. These findings suggest that the symptomatic benefits of indomethacin and related drugs in inflammatory arthritis may be achieved at the expense of significant adverse effects on joint tissues.